Efforts to Remove Thread under General Anesthesia after Cleft Lip Repair - OKUMURA, Yoshiyuki (Journal of Japanese Cleft Palate Association, 2020)
Background: Children have a physiologically higher oxygen consumption at rest, lower functional residual capacity, and anatomically shorter neck compared to their larger head, smaller nostrils, larger tongue, and enlarged tonsils, which are considered to cause airway obstruction, respiratory depression, and hypoxia. In addition, the frequency of sedative cardiac arrest in children is said to be equivalent to that under general anesthesia, and sedation is known to have a high risk. On the other hand, the removal of unsettled thread is a burden not only on the patient and their family, but also on medical personnel, involving restraint and pain.　Purpose: In our department, post-operative thread removal of cleft lip repair and secondary lip repair are performed under general anesthesia in the operating room. We review the details of general anesthesia under general planned hospitalization, and report the points of the procedure.　Subjects/Methods: Primary cleft lip repair was performed in our department for 11 years from January 2008 to December 2018, and threads were removed under general anesthesia in 9 of 22 cases. We explained the procedure and performed the operation for those cases who agreed.　The method of anesthesia, time of anesthesia, time of thread removal, and complications were retrospectively investigated based on medical records.　Results: The anesthesia method was GOS （Gas, Oxygen, Sevoflurane: dinitrogen oxide, oxygen, sevoflurane） in all cases. The mean anesthesia time was 13 minutes 43 seconds, and the mean thread removal time was 6 minutes 27 seconds. There were no serious complications such as cardiac arrest, delayed awakening and respiratory problems.　Discussion and Conclusion: Thread removal performed under the supervision of an anesthesiologist who is used to observing patients in a state of anesthesia and who is experienced in airway maintenance technology, ensures safety compared with suture removal under self-administered sedation. In addition, because the procedure ended on a predetermined date, it seemed to be effective in reducing the physical and psychological burden on patients and their families as well as medical workers.